2005
DOI: 10.1117/12.638181
|View full text |Cite
|
Sign up to set email alerts
|

Damage behavior of HfO 2 monolayer film containing gold nanoparticles as artificial absorbing defects

Abstract: Hafnia is one of the most utilized high-index materials in thin-film multilayer coatings for high-power lasers. It is well established that in the 2 2HfO SiO multilayers for 351 nm, nanosecond-pulse applications the damage is driven by the nanoscale absorbers localized in the hafnia layers. In this work, damage-crater formation thresholds and morphology are investigated for the undoped HfO 2 monolayer films and films containing isolated gold nanoparticles of 2-and 5-nm average diameter. Atomic force microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, it is very important to identify the damage defects and to study the characteristics of the damage. Some effort has been made to identify and characterize defects that limit the critical incident fluence [2], and many articles have reported that nano-gold particles were embedded in HfO 2 film to simulate the damage characteristics of nanoabsorbers and indicated that the most likely nanoabsorbers were localized Hf clusters [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to identify the damage defects and to study the characteristics of the damage. Some effort has been made to identify and characterize defects that limit the critical incident fluence [2], and many articles have reported that nano-gold particles were embedded in HfO 2 film to simulate the damage characteristics of nanoabsorbers and indicated that the most likely nanoabsorbers were localized Hf clusters [12].…”
Section: Introductionmentioning
confidence: 99%